Testing Small Ruminants for Mastitis Using the California Mastitis Test (CMT) and How to Properly Hand-Milk Goats: AN382/AN382, 02/2022 - Toledo, Izabella; Dacey, Justina Jade (EDIS, 2022)
This publication provides two step-by-step guides: one for testing small ruminants for mastitis using the CMT, and another for hand-milking goats. Written by Izabella Toledo and Justina Dacey, and published by the UF/IFAS Department of Animal Sciences, February 2022.